Pendampingan Pengembangan Laboratorium Virtual bagi Guru Kimia SMA di Kota Palembang - Sari, Diah Kartika; R, Ibrahim A; Hadeli, Muhammad; Ad’hiya, Eka (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this service activity is to provide assistance to high school/vocational high school/MA chemistry teachers in Palembang City, South Sumatra to develop a Virtual Laboratory. The implementation of the community service activity is carried out through a workshop which includes giving assistances in the development and designing of a virtual laboratory by the chemistry teachers who have been divided into several groups. The instrument used for evaluating the activity is an expert validation sheet, analyzed with Aiken, and translated descriptively. The results of this community service activity show that the design of a SMA Chemistry virtual laboratory has been obtained, which are in class X there are 12 materials grouped into 4 projects, in class XI there are 6 materials grouped into 6 projects, and in class XII there are 4 materials grouped into 4 projects. The results of the evaluation of the virtual laboratory developed by the teacher have been tested by expert validation and declared valid and feasible to continue to the implementation stage.